BIOREMEDIATION IN PETROLEUM CONTAMINATED SOIL TREATMENT USING PLANT-MICROORGANISMS COMBINATION (Case Study: Reduction Level of TPH and BTEX in Bioremediation Process) - Cut Nanda Sari; Tyas Putri Sativa; Setyo Sarwanto Moersidik (Testing Center for Oil and Gas LEMIGAS, 2016)
Oil spills, in both aquatic and terrestrial environments, are very detrimental to people and theÂ environment due to hydrocarbon compounds that are contained in oil which are not only be harmful for the balance of the ecosystem and the environment but also carcinogenic to humans and animals. Therefore remediation needs to be done. One of the methods is by using a combination of microorganisms and plants. The aim of this research is to analyze the inô€ƒ€ uences between several different treatments that are applied for TPH and BTEX removal in the process of remediation. In this research, bioremediation was conducted by using four different treatments which are: by adding compost (C), plants and compost (P), microorganisms and compost (B), and compost, plants and microorganisms (BP), to soil with oil content of 5% and 10%. The following test results of TPH in soil contaminated with 5% oil content are: 2.10% (C); 1.31% (B); 1.66% (P); and 0.68% (BP). The TPH test results in soil contaminated with oil content of 10% are: 3.30% (C); 2.54 (B); 3.91% (P); and 3.31% (BP). The highest percentage of TPH degradation in contaminated soil of 5% oil content was found in BP treatment (87.1%), while in the contaminated soil of 10% oil content the largest TPH removal percentage is by the treatment of adding bacteria (B) which is 76.19%. BTEX removal percentage in 5% oil contaminated soil in BP treatment is 68.35% while in 10% oil contaminated soil with B treatment the removal percentage is 84.91%. Based on statistical tests, both on contaminated soil with 5% and 10% oil content, TPH degradation signiô€‚¿ cantly affects the pH value as p < 0.05 but TPH degradation does not affect temperature values as p > 0.05.